English reading habit and comprehension among private middle school students - Simanungkalit, Ate Gueen Lasni Roha; Katuuk, Regina Oxania (Universitas Jambi, Indonesia, 2025)
The decline in reading habits and comprehension has become a growing concern among educators and researchers in Indonesia. This study aimed to describe and correlate the English reading habit and comprehension levels. The respondents were 94 students-grade students in Minahasa Utara Regency, Indonesia. This study utilized a quantitative approach, using descriptive and correlation statistical analysis of the collected numeric data. The analysis outcomes showed that the respondents indicated a low level of English reading habit and a moderate level of English reading comprehension. Notably, the study revealed that there was no significant correlation between students’ reading habit and their English reading comprehension level. These findings suggest that other factors may contribute to their comprehension skills, which may require further studies.